Evaluation of predictive value and changes of 99mTc-MIBI clearance and myocardial perfusion in patients with heart failure and indications for cardiac resynchronization therapy - A. I. Mishkina; T. A. Atabekov; A. S. Platonov; S. I. Sazonova; R. E. Batalov; K. V. Zavadovsky (Российский кардиологический журнал)
Aim. To study the significance of 99mTc-MIBI washout rate as a scintigraphic marker of mitochondrial dysfunction in predicting the effectiveness of cardiac resynchronization therapy (CRT), and to evaluate the long-term effect of CRT on 99mTc-MIBI clearance and myocardial perfusion.Material and methods. The study included 30 patients with heart failure of non-ischemic origin and indications for CRT. Before CRT, patients underwent 99mTc-MIBI myocardial perfusion scintigraphy (MPS) at rest. To assess the 99mTcMIBI washout rate, scanning was performed twice (after 1 hour and 3 hours). In addition, we assessed the severity of perfusion defects, contractility and mechanical desynchrony of the left ventricle (LV). All patients were rehospitalized after six months to assess the effectiveness of treatment and to perform MPS to assess the changes of scintigraphic parameters. According to echocardiography data, patients were divided into responders and non-responders. The criterion for a positive response to CRT was a decrease in LV end-systolic volume by 15% or more and/or an increase in LV ejection fraction by 10% or more.Results. Of all patients included in the study group, 23 (77%) were CRT responders. In this group of patients, the initial LV contractility indices were higher, and mechanical cardiac desynchrony was less pronounced compared to nonresponders. There were no significant differences in the 99mTc-MIBI washout rate and the severity of LV perfusion defect between responders and non-responders. Only in the responder group a significant decrease in the perfusion defect size was noted 6 months after CRT from 6 (3-9) points to 3 (3-4) points (p=0,0001), in contrast to non-responders (from 5 (4-8) to 6 (4-7), p=0,55). 99mTc-MIBI clearance decreased in both groups.Conclusion. Baseline 99mTc-MIBI washout rates did not demonstrate predictive value in determining CRT responders. This intervention has a positive effect on LV perfusion and contractility.